INDUSTRI KREATIF INDONESIA: PENDEKATAN ANALISIS KINERJA INDUSTRI - Ahmad Kamil (Trunojoyo University of Madura, 2015)
In 2008, the Department of Commerce of the Republic of Indonesia has launched a creative economic development documents interpreted the 2025 Indonesia became the starting point and guide the development of the creative economy in Indonesia. With the existence of this document, the industry and its stakeholders or other stakeholders can readily develop the creative economy in Indonesia. Economic development in the direction of the creative industries is one manifestation of optimism aspiration to support the Master Plan for the Acceleration and Expansion of Indonesia's Economic Development in realizing the vision of Indonesia are being developed nation.The main objective of this study is the first to analyze the role of the creative industries in Indonesia for labor, value added and productivity, secondly, to analyze the performance trend of the creative industries sector, and third, to analyze the factors affecting the performance of the creative industries sector in Indonesia. Under Indonesia Standard Industrial Classification (ISIC) and codes 151-372 (manufacturing industries category) identified 18 industry groups belonging to the creative industries, showed that the performance of the national creative industries has been relatively high (in terms of trend analysis of the performance of the industrial creative). Furthermore, regression analysis of panel data (econometrics) indicates that company size (SIZE), wages for workers (WAGE) and the content of local inputs (LOCAL) has a significant impact on the performance of Indonesia's creative industry. Meanwhile, the concentration ratio (CR4) no consequences but have koresi significantly positive effect on the performance of Indonesia’s creative industry.